Mechanical Model of a Hybrid Non-linear Viscoelastic Material Damping Device With Its Verifications - Zhou, Ying; Chen, Peng; Gong, Shunming (Frontiers in Materials, 2019)
This paper proposes a new viscoelastic (VE) material damping device with hybrid non-linear properties. Compared with traditional linear material dampers, the new non-linear VE material damping device is characterized by its better energy dissipation and deformation capability. The series performance tests of the VE device are conducted, based on which the sources and variation law of material non-linearities are analyzed. Five aspects of material non-linearities are summarized, including the shape change of hysteresis loop caused by phase difference, the initial stiffness caused by large loading rate, the softening effect caused by high temperature and fatigue, and the softening and stiffening effect under large strain deformation. A mechanic model for this device is proposed which considers multiple non-linear effects of the material. For the verifications of the proposed mechanic model, a shaking table test on a steel frame equipped with the new VE devices is designed and performed. Based on the proposed mathematic mechanic model, the numerical mechanic model is implemented in the OpenSees software. The accuracy of the mechanic model is firstly verified by comparing the performance tests data with the simulation results. Then the numerical model is also used to calculate the time history response of the shake table tested steel frame under earthquake loading. It is concluded that the mechanic model can well-depict several non-linear material behaviors of the new VE device, and the corresponding numerical model created in the open source calculation platform is reliable to be used to calculate non-linear time history response of a structure equipped with the new VE material damping devices.